In vitro activation of dinitrogenase reductase from the cyanobacterium Anabaena variabilis (ATCC 29413). - Böhm, I (1992)
Nitrogenase of the heterocystous cyanobacterium Anabaena variabilis was inactivated in vivo (S. Reich, H. Almon, and P. Böger, FEMS Microbiol. Lett. 34:53-56, 1986). Partially purified and modified (inactivated) dinitrogenase reductase (Fe-protein) of such cells was reactivated by isolated membrane fractions of A. variabilis or of Rhodospirillum rubrum, and acetylene reduction was measured. Reactivation requires ATP, Mg2+, and Mn2+. The activating principle is localized in the heterocyst and was found effective only when prepared from cells exhibiting active nitrogenase. It also restores the activity of modified Fe-protein from R. rubrum.